Early prevention of carrageenan-induced peripheral/spinal inflammation suppresses microglial hyperreactivity in the trigeminal spinal subnucleus caudalis and alleviates chronic facial nociception - Toru Yamamoto; Mitsuhiro Yoshida; Yuhei Koyama; Yatendra Mulpuri; Eiji Imado; Kana Oue; Mitsuru Doi; Yoshitaka Shimizu; Naotaka Kishimoto; Hiroshi Hanamoto; Kenji Seo (Heliyon)
In this study, we investigated the mechanisms underlying carrageenan-induced chronic pain and the therapeutic effect of the anti-inflammatory drug meloxicam. Rats were injected with 3 % carrageenan into the masseter muscle. These rats exhibited acute and chronic hypersensitivity to mechanical stimuli for 6 weeks after injection. Pre-treatment with meloxicam prevented carrageenan-induced chronic hypersensitivity. Furthermore, minocycline and dexamethasone, but not acetaminophen, suppressed carrageenan-induced hypersensitivity in the chronic phase. Microglial reactivity in the trigeminal spinal subnucleus caudalis (Vc) was assessed by immunohistochemistry 3 days after treatment. The reactivity of microglial cells in the Vc was increased in carrageenan-treated rats compared with vehicle-injected rats. Meloxicam and dexamethasone, but not acetaminophen, prevented carrageenan-induced microglial hyperreactivity in the Vc. These results suggest that early prevention of peripheral/spinal inflammation suppresses microglial reactivity in the Vc and inhibits the development of orofacial chronic pain.